Unraveling the role of the electron-pair density symmetry in reaction mechanism patterns: the Newman-Kwart rearrangement - Ayarde Henriquez, Leandro (Royal Society of Chemistry (RSC), 2022)
This work focuses on correctly identifying the topological signatures associated with the bond-breaking/ bond-forming processes along the versatile Newman–Kwart rearrangement. In contrast to recent reports and within the framework of the so-called bonding evolution theory, we show that only fold bifurcations emerge based on a detailed examination of the Hessian value at all potentially degenerate critical points and their relative distances along the pathway. The chemical implications of incorrectly classifying the nature of chemical events are outlined.
PUBLISHED